Folklore Motifs in Contemporary Short Fiction of Mozambique - V. A. Kuznetsova (Ибероамериканские тетради)
The article explores the role of folklore tradition in the short prose of modern Mozambique. The symbiosis of the European cultural matrix, inseparable from the language in which the work is written, and the oral heritage of the Mozambican people is analyzed on the material of one of Aldino Muianga’s short stories. The story «Rosa Maria» is included in the author’s debut collection «Xitala Mati», the main material for which became the folklore «scary stories» about witchcraft and the living dead. And while in his later works Muianga focuses on acute social plots of the colonial past and post-colonial present, in the world of «Xitala Mati» there is practically no place for white people: it is not colonizers and the colonized that interact there, but it is people and spirits. The text of «Rosa Maria» is filled with numerous «conventional signs» by means of which, in the paradigm of the traditional culture of the peoples of Mozambique, the world of the dead communicates with the world of the living. These signs are intuitive to the African reader, while the European must identify and decipher them. At the same time, «Rosa Maria» shows motifs and imagery characteristic of the Gothic novel, albeit reinterpreted and modified to suit African realities. Such components of the poetics as the encounter with the infernal in the image of a beautiful woman, the gloomy colouring supported by the landscape and ominous animals, and the interest in the emotional reactions of the characters, typical of Gothic literature, allow us to see in «Rosa Maria» a hybrid genre, the roots of which should be sought both in the European literary tradition and in the folk tales of Mozambique.